The Financial and Economic Effects of Geographical Restrictions Upon the Investment Policies of Life Insurance Companies - Beard, Winston Clingan (Journal of Finance, 1962)
Winston Clingan Beard, The Financial and Economic Effects of Geographical Restrictions Upon the Investment Policies of Life Insurance Companies, The Journal of Finance, Vol. 17, No. 4 (Dec., 1962), pp. 663-664